2012
DOI: 10.1155/2012/586348
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Protocols for Knee Joint Motion Analyses in the Stance Phase of Gait: Correlation of the Rigid Marker Set and the Point Cluster Technique

Abstract: Objective. There are no reports comparing the protocols provided by rigid marker set (RMS) and point cluster technique (PCT), which are similar in terms of estimating anatomical landmarks based on markers attached to a segment. The purpose of this study was to clarify the correlation of the two different protocols, which are protocols for knee motion in gait, and identify whether measurement errors arose at particular periods during the stance phase. Methods. The study subjects were 10 healthy adults. All esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…First, analyses of the rotational movement of the knee joint using motion analysis systems have associated problems in measurement precision according to skin movement artifacts [23,24]. The measurement method used in this study was confirmed to show repeatability in previous research by the authors [25], and also showed high correlations in comparisons with an existing measurement method (point cluster technique) [25]. Although the problem of whether the motion of the actual bone is reflected is still present, the non-invasive method used in this study is considered to produce reasonable results when compared with a previous study [26].…”
Section: Discussionsupporting
confidence: 68%
“…First, analyses of the rotational movement of the knee joint using motion analysis systems have associated problems in measurement precision according to skin movement artifacts [23,24]. The measurement method used in this study was confirmed to show repeatability in previous research by the authors [25], and also showed high correlations in comparisons with an existing measurement method (point cluster technique) [25]. Although the problem of whether the motion of the actual bone is reflected is still present, the non-invasive method used in this study is considered to produce reasonable results when compared with a previous study [26].…”
Section: Discussionsupporting
confidence: 68%
“…Six different common marker sets (Plug in Gait® (PiG) [4], rigid marker set with clusters (RMS) and without using clusters (RMS_oC) [5], six degree of freedom (6DOF) [6], Helen Hayes (HH) [6], functional approach (FAPA) [7]) were used. Therefore, 26 markers and two clusters were simultaneously attached to the subjects' lower limb and pelvis.…”
Section: Methodsmentioning
confidence: 99%
“…Body Segment CM places a marker on each body segment. Various tests have used these and other marker placements measured by optical tracking systems to measure motion [26], bone bending [27], or to compare rigid marker sets to point clusters (see Figure 3 (b)) [28] [29] to estimate anatomical landmarks based on markers attached to a segment. The rigid marker sets are meant to limit measurement errors due to muscle and skin motion [30], although when using many markers as shown in Figure 3 (b), errors were minimized.…”
Section: Literature Survey Of Human Body Measurementmentioning
confidence: 99%
“…[23] and (b) Rigid (left) versus point cluster (right) marker sets being used to measure gait. [28] Of key importance to all of the previous references is the notion of how certain and reliable are the measurements and the techniques used to make the measurements. For example, in the above list of normal maximum rotations from [20], it is unknown how the measurements were made and therefore, how much uncertainty there is in each measurement noting that the angles are nearly all listed in 10° increments.…”
Section: Literature Survey Of Human Body Measurementmentioning
confidence: 99%
See 1 more Smart Citation